Simulation in Wood Industry. Part I - Mihály Varga (University of Zagreb, Faculty of Forestry and Wood Technology, 2009)
The aim of our project was to answer the question of our multinational window and door hardware manufacturing company as to whether it was worth building a new hall and increase the output or not. Of course there were also other important questions to answer, such as what kind of array of manufacturing machines should be, what is the minimum number of employees (including employee redundancy), what is the right timing for incoming parts and outgoing products, etc. Such questions are usually hard to answer with classical methods. Therefore we have choosen other ways to solve the problem: the solution was to create a simulation model and simulate all processes in order to get the required results and answers. For this project we used the program SIMUL8 Company’s SIMUL8 Professional.